2023
DOI: 10.33975/riuq.vol35n1.1154
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term pathological effects of COVID-19 on the placenta during second trimester and labor.

Abstract: Background: COVID-19 pandemic has affected all the world. The consequence of the COVID-19 infection causes many disorders in many organs, one of them is the placenta. COVID-19 disease has long-term effects on various tissues after recovery. The aim of this study was to investigate the placentas of pregnant women with healthy, COVID-19 positive during the second trimester and labor. Material and methods: A total of twenty-four pregnant women (8 patients per each group) were included in the study. Their pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the literature, there are studies showing histopathologic changes caused by COVID-19 infection on both placenta and umbilical cord [12][13] . Apart from covid-19 infection, diseases such as preeclampsia also cause histologic changes in the placenta 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are studies showing histopathologic changes caused by COVID-19 infection on both placenta and umbilical cord [12][13] . Apart from covid-19 infection, diseases such as preeclampsia also cause histologic changes in the placenta 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that especially intervillous thrombosis fibril accumulation was prominent in the basal plaque layer and the distribution of lesions related to the degree of invasive subgroups of structures containing large-scale lacunae was significant 10 . Like placenta previa, preeclampsia and covid-19 infection also cause histologic changes in the placenta and umblical cord [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%